SmilODB: a multi-omics database for the medicinal plant danshen (Salvia miltiorrhiza, Lamiaceae) - Liu, Yong-Hui; Zeng, Wen-Qiong; Tao, Si-Fan; Du, Yi-Nuo; Yu, Fei-Hong; Qi, Zhe-Chen; Yang, Dong-Feng (Frontiers in Plant Science, 2025)
IntroductionSalvia miltiorrhiza Bunge (Danshen) is a traditional medicinal plant widely used in the treatment of cardiovascular and inflammatory diseases. Although various omics resources have been published, there remains a lack of an integrated platform to unify genomic, transcriptomic, proteomic, and metabolomic data.MethodsTo address this gap, we constructed the S. miltiorrhiza Multi-omics Database (SmilODB, http://www.isage.top:56789/), which systematically integrates publicly available genome assemblies, transcriptome datasets, metabolic pathway annotations, and protein structural predictions. Protein structures were predicted using the RoseTTAFold algorithm, and all data were visualized using interactive heat maps, line charts, and histograms.ResultsSmilODB includes: (i) two genome assemblies of S. miltiorrhiza, (ii) 48 tissue-specific transcriptome datasets from root, leaf, and other vegetative tissues, (iii) annotated biosynthetic pathways for bioactive compounds such as tanshinones and salvianolic acids, and (iv) 2,967 high-confidence protein models. The database also integrates bioinformatics tools such as genome browsers, BLAST, and gene heatmap generators.DiscussionSmilODB provides an accessible and comprehensive platform to explore multi-omics data related to S. miltiorrhiza. It serves as a valuable resource for both basic and applied research, facilitating advances in the understanding of this medicinal plant’s molecular mechanisms and therapeutic potential.